2016
DOI: 10.1177/0022466915624413
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Placement in Special Education and Adult Well-Being

Abstract: The present study investigates the relationship between childhood placement in special education and adult well-being among 1,377 low-income, minority children participating in the Chicago Longitudinal Study. Roughly 16% of the sample received special education services in grades 1-8. After accounting for sociodemographic factors and early academic achievement, children receiving special education services tended to have lower rates of high school completion and fewer years of education, as well as greater rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…Other measures of school failure, including grade retention and delayed high school graduation, have also been linked to increased risk for later mental health problems (e.g., Melkevik et al, 2016; Robles-Piña, Defrance, & Cox, 2008). Previous research has also indicated that special education participants exhibit higher rates of depression in emerging adulthood than their peers, and that this relationship is mediated by academic achievement (Chesmore, Ou, & Reynolds, 2016). …”
Section: Risk Promotive and Protective Factors For Depressionmentioning
confidence: 98%
“…Other measures of school failure, including grade retention and delayed high school graduation, have also been linked to increased risk for later mental health problems (e.g., Melkevik et al, 2016; Robles-Piña, Defrance, & Cox, 2008). Previous research has also indicated that special education participants exhibit higher rates of depression in emerging adulthood than their peers, and that this relationship is mediated by academic achievement (Chesmore, Ou, & Reynolds, 2016). …”
Section: Risk Promotive and Protective Factors For Depressionmentioning
confidence: 98%
“…These actions can serve as gateway mechanisms if they change a student’s eventual educational attainment. However, evidence on whether this is in fact the case is mixed (Chesmore, Ou, & Reynolds, 2016; Martorell & Mariano, 2018). Another institutional pathway through which some ECE programs may operate is via their influence on the subsequent schools children attend.…”
Section: Mechanisms For Persistencementioning
confidence: 99%
“…This result is inconsistent with earlier reports that children with disabilities who attended special schools have lower QoL in adulthood than their peers who attended inclusive or mainstream schools (Eckhart, Haeberlin, Lozano, & Blanc, ; Myklebust & Båtevik, ). It was also demonstrated that adults who attended special schools have lower educational attainment, are less likely to gain professional qualifications, are less likely to be in paid employment and earn less (Chesmore et al., ; Eckhart et al., ; Myklebust & Båtevik, ). Consequently, their self‐esteem is lower than that of their peers who attended mainstream schools (Eckhart et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of attending a special school are equivocal. Special instruction and other forms of support may increase pupils’ competencies (Hanushek, Kain, & Rivkin, ), but attending a special school inevitably attracts a disability label (Chesmore, Ou, & Reynolds, ). This label may lead to stigmatization, which negatively affects life outcomes in adulthood through two psychosocial mechanisms: society's lower expectations towards persons with disabilities and the lowering of their self‐confidence and achievement motivation.…”
Section: Introductionmentioning
confidence: 99%